A model-based methodology for rapid designing of hydraulic breakers. Issue 2 (4th May 2017) - Franco, Walter; Ferraresi, Carlo
Abstract: The design and dimensioning of a hydraulic breaker with nitrogen spring is often carried out on the base of tradition and empirical considerations. This article proposes a methodology dedicated to such breakers that, with a simplified procedure, allow a rapid determination of the main dimensions of piston and spring, starting from the required performance, namely: the impact energy and work frequency. The method is based on a simplified mathematical model of the breaker and has been validated by means of experimental test on commercial breakers.